BRICS media : reshaping the global communication order? - Thussu, Daya Kishan; Nordenstreng, Kaarle (Abingdon, Oxon ; New York, NY : Routledge, Taylor & Francis Group, 2021)
"Bringing together distinguished scholars from BRICS nations and those with deep interest and knowledge of these emerging powers, this collection makes a significant intervention in the ongoing debates about comparative communication research and thus contribute to the further internationalization of media and communication studies. The unprecedented expansion of online media in the world's major non-Western nations, exemplified by BRICS (Brazil, Russia, India, China and South Africa) is transforming global communication. Despite their differences and divergences on key policy issues, what unites these five nations, representing more than 20 per cent of the global GDP, is the scale and scope of change in their communication environment, triggered by a multilingual, mobile Internet. The resulting networked and digitized communication ecology has reoriented international media and communication flows. Evaluating the implications of globalization of BRICS media on the reshaping of international communication, the book frames this within the contexts of theory-building on media and communication systems, soft power discourses and communication practices, including in cyberspace. Adopting a critical approach in analysing BRICS communication strategies and their effectiveness, the book assesses the role of the BRICS nations in reframing a global communication order for a 'post-American world'. This critical volume of essays is ideal for students, teachers and researchers in journalism, media, politics, sociology, international relations, area studies and cultural studies programmes"--
Part I. Challenging dominant discourses in a new world order -- Part II. Media and communication structures and systems -- Part III. BRICS and global strategic communication -- Part IV. BRICS and changing communication practices.
OCLC-licensed vendor bibliographic record.
Keywords: BRICS; Intercultural communication -- Developing countries; Communication -- Political aspects -- Developing countries; Mass media -- Political aspects -- Developing countries; Developing countries -- Foreign relations; SOCIAL SCIENCE / Media Studies